2020
DOI: 10.1186/s13014-020-01617-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning vs. atlas-based models for fast auto-segmentation of the masticatory muscles on head and neck CT images

Abstract: Background: Impaired function of masticatory muscles will lead to trismus. Routine delineation of these muscles during planning may improve dose tracking and facilitate dose reduction resulting in decreased radiation-related trismus. This study aimed to compare a deep learning model with a commercial atlas-based model for fast autosegmentation of the masticatory muscles on head and neck computed tomography (CT) images. Material and methods: Paired masseter (M), temporalis (T), medial and lateral pterygoid (MP,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 37 publications
(57 reference statements)
3
35
1
Order By: Relevance
“…It is noteworthy that a minority of respondents (6/34) reported use of deep-learning-based AC, which has been shown in the literature to be significantly more accurate than other methods. 11,38,39 Therefore, a broader availability of deep-learning-based tools could facilitate a broader use of AC in the clinic. A strong majority of respondents thought that it was difficult to modify the output of an automated planning algorithm and this limited the algorithms' usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a minority of respondents (6/34) reported use of deep-learning-based AC, which has been shown in the literature to be significantly more accurate than other methods. 11,38,39 Therefore, a broader availability of deep-learning-based tools could facilitate a broader use of AC in the clinic. A strong majority of respondents thought that it was difficult to modify the output of an automated planning algorithm and this limited the algorithms' usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown improvements in different treatment sites (e.g. head-and-neck ( 38 40 ), prostate ( 39 , 41 ), rectum ( 42 ), whole body ( 43 )). However, abdominal organs present additional challenges including strong interpatient variability, bowel loop displacements and hollow organs, which causes AI studies still report similar results to those achieved in our current study ( 10 , 44 – 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various autosegmentation methods that have historically been applied to computed tomography (CT) images have shown promise on MRI [6], including deformable image registration (DIR)based structure propagation [4,7], atlas-based autosegmentation [8][9][10], and deep learning [11][12][13]. While several studies have shown that deep learning can improve organ-at-risk (OAR) segmentation accuracy compared to atlas-based autosegmentation on CT for head and neck [14][15][16] and other treatment sites [17][18][19][20], to our knowledge, only a single study thus far has directly compared these methods on MRI for any treatment site [21]. As MR-guided adaptive RT becomes more accessible, evaluating these autosegmentation methods on MRI is crucial.…”
Section: Introductionmentioning
confidence: 99%